2018
DOI: 10.20944/preprints201808.0443.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Different Supplementary Light Sources on the Quality of Grafted Tomato Seedlings and the Expression of Two Photosynthetic Genes

Abstract: Supplementary lighting is commonly used in high-quality seedling production. In this study, grafted tomato seedlings were grown for 10 days in a glasshouse with a 16-hour daily supplementary lighting at 100 μmol·m−2·s−1 PPFD from either high pressure sodium (HPS), metal halide (MH), far-red (FR), white LEDs (W), or mixed LEDs (W1R2B1) to determine which light sources improve the seedling quality. The control did not have any supplementary light. The physiologica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Phytochrome (R and FR photoreceptor) is known to regulate lateral root formation by manipulating the distribution of auxin which can cover long distances from the shoot to the root (Salisbury et al, 2007). Wei et al (2018) found greater root length and fresh weight of grafted tomato seedlings treated with W1R2B1 LED compared to W or FR LEDs, HPS, metalhalide or natural light. Similarly, basil cv.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phytochrome (R and FR photoreceptor) is known to regulate lateral root formation by manipulating the distribution of auxin which can cover long distances from the shoot to the root (Salisbury et al, 2007). Wei et al (2018) found greater root length and fresh weight of grafted tomato seedlings treated with W1R2B1 LED compared to W or FR LEDs, HPS, metalhalide or natural light. Similarly, basil cv.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, red and blue lights have higher absorption rates compared to green light which penetrates the leaves and reaches deeper in the plant canopy (Kozai et al, 2015). Greater root system development, biomass formation, and relative chlorophyll content of grafted tomato seedlings were reported under white (W) or W1R2B1 LED compared to HPS, metal-halide, far-red LEDs or no supplemental lighting in a greenhouse (Wei et al, 2018). Moreover, shoot and root dry weight of cucumber seedlings were found greater under RB LEDs compared to FL lamps (Marques da Silva et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation